Experimental Endoscopic Angular Domains of Transnasal and Transoral Routes to the Craniovertebral Junction: Light and Shade. Issue 8 (April 2016) - Visocchi, Masimiliano; Pappalardo, Gaetano; Pileggi, Marco; Signorelli, Francesco; Paludetti, Gaetano; La Rocca, Giuseppe
Abstract : Study Design: We investigate on the surgical reliability of nasal palatine line for the transnasal approach and introduce a conceptually analogue radiological line as a reliable predictor of the maximal superior extension of the transoral approach. We have also compared radiological and surgical lines to find possible radiological references points to predict preoperatively the maximal extent of superior dissection for the transoral approach. Objective: After comparing the surgical exposition angle and the working channel volume of both the approaches in our previous article, now we compare the radiological (theoretical) with the "surgical" (effective) Nasopalatine line and the latter with the recently introduced Nasal Axial Line. We conceived a radiological line with a similar significance for the transoral approach and we called it Mandibulopalatine line; then we compared the radiological with the "surgical" one. Summary of Background Data: Endoscopy represents both an alternative and a useful complement to the standard microsurgical approach to the anterior craniovertebral junction (CVJ). Both the surgical routes have a limitation caused by the hard palate. Methods: Ten fresh nonperfused cadavers were studied. Transnasal and transoral linear and angled exposure of the CVJ were evaluated by means of X-ray and CT scan in the sagittal plane. Results: The angular difference between the radiological and surgical transoral endoscopic lines was significantly smaller compared with the difference between the radiological and surgical transnasal lines. Finally we found how to calculate preoperatively the "surgical" (effective) Mandibulopalatine line by a simple lateral preoperative radiological study of the CVJ. Conclusion: Naso-axial line is confirmed to be a reliable preoperative predictor of the maximal extent of inferior dissection for transnasal approach. Surgical Palatine Inferior dental Arch line will draw the maximal extent of superior dissection for the transoral approach with simple lateral head X-ray examination by open mouth. Level of Evidence: 3